Analisis Pola Musik Karawitan di Tengah Era Digital - Firman; Firdaus; Halim, M.; Alfalah; Sriyanto (AI Society & STMIK Indonesia, 2024)
Traditional arts, especially musical music, are facing challenges in the digital era and the influence of foreign cultures. Efforts continue to be made to combine technology with traditional arts. The method adopted in this research is library research, which involves collecting data and information in depth through various references such as books, magazines, other references, and research results. This research explains the adaptation of Karawitan music patterns to modern technology and its impact on the interests of the younger generation. Use of digital musical instruments to create innovative compositions that combine traditional elements with contemporary elements. The role of the community in supporting the preservation of Karawitan art is also emphasized, with active participation in traditional music events and efforts to promote the culture to others. In conclusion, this article emphasizes the complexity of the relationship between tradition and innovation in the context of Karawitan music in the era of modern technology.